Wellness Tourism Model in Recovery Sector Tourism in Belitung during the New Normal Period - Valeriani, Devi; Wibawa, Dian Prihardini; Safitri, Revy; Apriyadi, Rion (Jurnal Penelitian Pariwisata, 2022)
Belitung Regency is the district that determines tourism as the main sector. Development tourist experiences drop in aspect economy, employment, and tax for an area with the Covid-19 pandemic. This research focuses on and aims to analyze how the Wellness Tourism model in the recovery of tourism in Belitung Regency during the new normal period. The results showed that model Wellness Tourism starts from the application of Wellness Tourism indicators, namely (1) High Standard Sanitation; (2) High Standard Security; (3) Staycations; (4) Niche Tourism; (5) Private Travel Tours; (6) Virtual Tourism. Each indicator is related to Transportation, Food, Activities, Healthy, Promotional Services, Rooms, Management, and Environment. Hotels and Destinations must carry out development and revitalization so that they can continue to grow so that Immersion, Spiritual, and Community are built when tourists travel. Keywords: Wellness Tourism Model, Tourism Industry, New Normal